Academic library use and student retention: A quantitative analysis - Haddow, Gaby (Elsevier, 2013)
A key component of Vincent Tinto's model of retention is the importance of student integration in the academic institution. Library use can be regarded as a form of integration within such institutions. A quantitative approach was applied to demonstrate how institutional data can be combined to examine library use and retention at a single institution. Undergraduate student and library use data were analyzed to identify results that suggested associations between library use and student retention. Library use was measured by log-ins to electronic resources, as well as borrowing from the library. The undergraduate students enrolled for the first time in 2010 comprised the population, Sub-group student characteristics, age and socioeconomic status, underwent further analysis. The findings show retained students log-in to authenticated resources and borrow from the library at higher rates than withdrawn students. Mature age students withdraw from the university at higher rates than younger students. Log-ins to authenticated resources increase as students progress over time through their university programs. No notable associations were found among socioeconomic background, library use, and retention. For the institution, these findings can inform the development of library services to target specific student groups on the basis that higher library use may lead to improved integration and retention. In addition, the study describes a research design that is replicable in other institutions and contributes to library use and retention literature.